Good Governance and Development - Smith, Brian C. (Basingstoke, New York Palgrave Macmillan, 2007)
Brian Smith offers an exploration of the implications of the 'good governance' agendas for developing and newly democratised countries.
Include Index and Bibliography
Keywords: Political corruption--Prevention -- Public administration -- Developing countries